Analysis of the Implementation of Standard Operating Procedures in the Implementation of Work for Terminal Operation Center Employees of PT. Angkasa Pura II at Soekarno-Hatta International Airport - Werdian Yogi Pratikno; Awan Awan (CV. Rayyan Dwi Bharata, 2023)
Soekarno-Hatta International Airport is the largest and busiest airport which has 4 terminals under its supervision. PT.Angkasa Pura II formed a new unit, namely the Terminal Operatin Center unit, a new TOC unit which was established in mid-September 2018. This study aims to analyze the application of SOP Terminal Operation Center in implementing the work of its employees and what are the obstacles encountered in implementing the Terminal Operation Center SOP. This study uses qualitative research methods using data collection techniques including observation, interviews, and documentation using data analysis techniques in the form of data collection, data reduction, data presentation (data display), and drawing conclusions. The research was carried out at the Terminal Operation Center Unit at Soekarno-Hatta International Airport. The results of the study found that the implementation of SOPs had not been implemented 100 percent, SOPs had not been implemented since the establishment of the TOC and there were also obstacles encountered in implementing the SOPs, namely the lack of human resources, both internal TOC and entities.